Factors Influence Financial Sustainability Banking In Indonesia - Arini Mar'ah Sholikah; Titis Miranti (Al-Tijary, 2020)
This research aims to determine the factors that affect the financial sustainability of conventional banks and sharia banks in Indonesia. Data obtained from the financial statements of conventional commercial banks and Islamic commercial banks have been published by the Financial Services Authority (OJK) for the period 2014 to 2018. The total population used in this study are all conventional and Sharia banks that publish their financial statements on the OJK. The research variables used include Financial Self Sufficiency (FSS) as the dependent variable. Return on assets (ROA), Cash to deposits (CTD), Loans to assets (LTA), Deposits to assets (DTA) as independent variables. The analysis used is the tree classification. The tree classification method requires the dependent variable in the form of categorical data. Processing results show that three financial performance factors affect financial sustainability, namely ROA, LTA, and DTA. Error in the analysis process is 29%. So that the accuracy of using the tree classification method in predicting the factors that affect banking financial sustainability is 71%.